Service redundancy and cluster-based routing protocols for wireless sensor and mobile ad hoc networks: a survey - Yagoub, Mudathir F.S.; Rodrigues, Joel J. P. C.; Khalifa, Othman Omran; Mohammed, Abuagla B.; Korotaev, Valery (John Wiley and Sons Ltd, 2020)
Service discovery (SD) is the cornerstone of wireless and mobile systems. The discovery of effective service is the key to achieve a higher level of ubiquity, which ensures the availability of services to users and applications significantly, and the high use of services. The research in this field is limited, with a few SD protocols available for specific purposes specified in the 6LoWPAN region. This paper discusses the various issues and challenges facing the design and selection of the appropriate service discovery and cluster-based mechanism. Moreover, attention has been drawn to the cross-layer solution by discussing different clustering techniques used to solve the redundancy problems. Furthermore, the service discovery protocols and cluster-based routing protocols are critically investigated considering the redundancy problem, methods, mechanisms, and architectures by categorizing them into different categories, comparing them with fundamental parameters in the WSNs and MANETs environments. In addition, a modern form is proposed to show the life cycle of the service discovery process, and a new figure has been designed to clarify to the researchers various of the open issues related to the service discovery and cluster-based routing protocols, corresponding objectives and the techniques of solving problems. Through the discussion of the scientific papers under survey, important results and valuable recommendations were reached. The survey is concluded with a summary, open research issues, outlook, and directions for future research on the topic.